2004
DOI: 10.5194/angeo-22-1595-2004
|View full text |Cite
|
Sign up to set email alerts
|

Global auroral conductance distribution due to electron and proton precipitation from IMAGE-FUV observations

Abstract: Abstract. The Far Ultraviolet (FUV) imaging system on board the IMAGE satellite provides a global view of the north auroral region in three spectral channels, including the SI12 camera sensitive to Doppler shifted Lyman-α emission. FUV images are used to produce instantaneous maps of electron mean energy and energy fluxes for precipitated protons and electrons. We describe a method to calculate ionospheric Hall and Pedersen conductivities induced by auroral proton and electron ionization based on a model of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 57 publications
(96 reference statements)
2
46
1
Order By: Relevance
“…This assumption is based on the effect of particle precipitation which gives rise to intense auroral emissions and high conductivity in the auroral zone (Evans et al 1977;Vondrak & Robinson 1985;Fuller-Rowell & Evans 1987;Coumans et al 2004, and many others). While conductivity is essential to Joule heating of ions, it was not until comparisons of energy input from solar radiation, electromagnetic waves in the form of Poynting flux, and particle precipitation were carried out that the relative contributions to the IT energy budget were realized (Knipp et al 2004;Huang et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is based on the effect of particle precipitation which gives rise to intense auroral emissions and high conductivity in the auroral zone (Evans et al 1977;Vondrak & Robinson 1985;Fuller-Rowell & Evans 1987;Coumans et al 2004, and many others). While conductivity is essential to Joule heating of ions, it was not until comparisons of energy input from solar radiation, electromagnetic waves in the form of Poynting flux, and particle precipitation were carried out that the relative contributions to the IT energy budget were realized (Knipp et al 2004;Huang et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…The value of the W i /W e ratio is about 11% under quiet conditions and decreases to about 4% at |AL| = 1000 nT. It was already noted earlier that the ion pre cipitation contribution to the total energy release tends to decrease with increasing magnetic activity (Coumans et al, 2004): these authors reported that the proton contribution to the total ionospheric conduc tance was higher in the quiet periods compared to the substorms.…”
Section: Planetary Characteristics Of Ion Precipitationsmentioning
confidence: 68%
“…Jointly with the data of magnetometric obser vations, these models make it possible to obtain the global distribution pattern of electrical fields and field aligned currents and to estimate Joule heating of the ionosphere. Various computational techniques and simulation results for ionospheric conductance are dis cussed in many publications, for example, in (Robinson et al, 1987;Brekke and Moen, 1993;Galand and Rich mond, 2001;Coumans et al, 2004;Nikolaeva et al, 2014). Figure 7 presents the distributions of total Hall conductance produced by both electron and ion pre cipitations.…”
Section: Ionospheric Conductancementioning
confidence: 99%
“…In order to aid the interpretation of this value of a, let us first estimate its likely bounds. Since the substorm magnetic bay magnitude is equal to the minimum value of the synthetic IL index during the expansion phase it is reasonable to assume that: (a) the contributing station is between 20:29 MLT and 01:15 MLT (the ±1 standard deviation limits of the probability distribution of onset MLT for the TEA substorms) and at λ=70 • (the most common magnetic latitude of the minimum IL for the TEA substorms); (b) the polar cap boundary is at the same magnetic latitude, in order that the contributing station is at the latitude where the eastward equivalent current minimises in the AL 2 model; and (c) the height-integrated Hall conductivity H =15 Siemens, as measured in the midnight MLT sector during the expansion phase of an individual substorm (Coumans et al, 2004) and comparable to the conductivity measured for a statistical ensemble of 28 isolated substorms when averaged over the ensemble and over the whole substorm region (Gjerloev and Hoffman, 2000). Let us also assume that: (d) the simple convection pattern associated with Eqs.…”
Section: The Directly-driven Component -Almentioning
confidence: 99%